(untitled) (Pakistan Journal of Scientific Research, 2023)
Designing a POS system that enables the FBR to keep a record of the transactions made at the Tier-1 retailers who fall under the tax ruling of FBR. This will enable the FBR to check how much tax is being collected from the consumer. With that record, they will be able to estimate how many people are filled and what it enables to collect tax from the retailers with the help of FBR invoice number that will generate in real-time when the receipt is generated for the shopping consumer. Datamining techniques are effective in uncovering the previously hidden patterns for storing the data these techniques can be applied in every field such as banking, agriculture, and marketing. Several different data mining techniques have been used to improve the performance and predictions of exciting data. The novelty of the proposed system is that different data mining techniques get time stamps on yearly and monthly based transactions which gives us different variations-based graphs with precise working of data mining techniques.